2019
DOI: 10.5194/cp-15-291-2019
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of sea ice albedo and insulation effects to Arctic amplification in the EC-Earth Pliocene simulation

Abstract: Abstract. In the present work, we simulate the Pliocene climate with the EC-Earth climate model as an equilibrium state for the current warming climate induced by rising CO2 in the atmosphere. The simulated Pliocene climate shows a strong Arctic amplification featuring pronounced warming sea surface temperature (SST) over the North Atlantic, in particular over the Greenland Sea and Baffin Bay, which is comparable to geological SST reconstructions from the Pliocene Research, Interpretation and Synoptic Mapping … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Since there is very little sea ice, more heat can be released, explaining the higher SAT in the Arctic during September to November. This was also seen in the study by Zheng et al (2019). The Hudson Bay shows a large temperature reduction during winter because it has been replaced by land which cannot stabilise the surface air temperature as much as water can (Hunter et al, 2019).…”
Section: Surface Air Temperaturesupporting
confidence: 68%
“…Since there is very little sea ice, more heat can be released, explaining the higher SAT in the Arctic during September to November. This was also seen in the study by Zheng et al (2019). The Hudson Bay shows a large temperature reduction during winter because it has been replaced by land which cannot stabilise the surface air temperature as much as water can (Hunter et al, 2019).…”
Section: Surface Air Temperaturesupporting
confidence: 68%
“…In marine and lacustrine sediments, bacterial brGDGTs were thought to originate predominantly from continental soil erosion arriving in the sediments through terrestrial runoff. More recent studies, however, have indicated that aquatically produced brGDGTs could be affecting the distribution of the sedimentary brGDGTs and thus the temperature estimates based upon them (Warden et al, 2016;Zell et al, 2013;Zhu et al, 2011). Since the discovery that sedimentary brGDGTs can have varying sources, different calibrations have been developed depending on the origin of the brGDGTs, i.e., soil calibration (De Jonge et al, 2014), peat calibration (Naafs et al, 2017) and aquatic calibrations (i.e., Foster et al, 2016;Pearson et al, 2011;Russell et al, 2018).…”
Section: Provenance Of Branched Gdgtsmentioning
confidence: 99%
“…Paleoclimate records from the Arctic indicate that the change in Arctic summer temperatures during past global warm periods was 3-4 times larger than global temperature change (Miller et al, 2010). While earth system models (ESMs) have been able to provide fairly accurate predictions of the modern amplification of Arctic temperatures hitherto observed for some time (Marshall et al, 2014), they have only recently implemented mechanisms that simulate Arctic amplification of temperature for past warm periods such as the Pliocene (2.6-5.3) with a convincing pattern of seasonality (Zheng et al, 2019). The success of earlier models at capturing modern warming, contrasted with the additions needed to simulate the Pliocene Arctic temperatures, suggest that the array of fast and slow feedback mechanisms have not fully manifested themselves for the modern Arctic, and perhaps there are still further feedback mechanisms we are yet to understand and implement in climate models.…”
Section: Introductionmentioning
confidence: 99%
“…As a practical diagnostic tool to analyse the role of various forcing and 152 feedback, CFRAM has been used widely in climate change research on 153 studying surface climate change (Taylor et al, 2013;Song and Zhang, 2014;154 Hu et al, 2017;Zheng et al, 2019). 155 156 This method has been applied to the middle atmosphere climate sensitivity 157 study as well (Zhu et al, 2016).…”
Section: ) 143 144mentioning
confidence: 99%